2014
DOI: 10.5194/hess-18-1189-2014
|View full text |Cite
|
Sign up to set email alerts
|

Separating precipitation and evapotranspiration from noise – a new filter routine for high-resolution lysimeter data

Abstract: Abstract. Weighing lysimeters yield the most precise and realistic measures for evapotranspiration (ET) and precipitation (P ), which are of great importance for many questions regarding soil and atmospheric sciences. An increase or a decrease of the system mass (lysimeter plus seepage) indicates P or ET. These real mass changes of the lysimeter system have to be separated from measurement noise (e.g

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 22 publications
0
65
0
3
Order By: Relevance
“…The lysimeter readings are affected by large random fluctuations caused by wind and other factors that influence the measurement. Therefore, the AWAT filter (Peters et al, 2014) in a second correction step was applied on the minute-wise summed leachate and on the weights for each individual lysimeter. First, the AWAT routine gathers information about signal strength and data noise by fitting a polynomial to each data point within an interval of 31 min.…”
Section: Lysimetermentioning
confidence: 99%
See 4 more Smart Citations
“…The lysimeter readings are affected by large random fluctuations caused by wind and other factors that influence the measurement. Therefore, the AWAT filter (Peters et al, 2014) in a second correction step was applied on the minute-wise summed leachate and on the weights for each individual lysimeter. First, the AWAT routine gathers information about signal strength and data noise by fitting a polynomial to each data point within an interval of 31 min.…”
Section: Lysimetermentioning
confidence: 99%
“…They pointed out that the adequate filter method for lysimeter measurements is still a challenge, especially at high temporal resolution, due the fact that noise of lysimeter measurements varies strongly with weather conditions and mass balance dynamics. Peters et al (2014) recently introduced a filter algorithm for high-precision lysimeters, which combines a variable smoothing time window with a noise-dependent threshold filter that accounts for the factors mentioned above. They showed that their Adaptive Window and Adaptive Threshold (AWAT) filter improves actual evapotranspiration and precipitation estimates from noisy lysimeter measurements compared to smoothing methods for lysimeter data using the Savitzky-Golay filter or simple moving averages used in other lysimeter studies (e.g., Vaughan and Ayars, 2009;Huang et al, 2012;Nolz et al, 2013;Schrader et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations